Teks Ucapan Yang Hormat Profesor Dato’ Dr. Daing Nasir Ibrahim Naib Canselor Universiti Malaysia Pahang Sempena Opening Ceremony of the National Geoscience Conference 2016 - Pejabat, Naib Canselor UMP (Universiti Malaysia Pahang, 2016)
We in Universiti Malaysia Pahang in particlular are very pleased to receive all delegates with the warmth of UMP hospitality and to host this conference to the best of our ability. In this regard, the organizing team from the Faculty of Engineering Technology has put the best of their efforts to ensure the success of NGC16.